Efficient evaluation of collisional energy transfer terms for plasma particle simulations. (10th February 2016) - Turrell, A. E.; Sherlock, M.; Rose, S. J.
Abstract : Particle-based simulations, such as in particle-in-cell (PIC) codes, are widely used in plasma physics research. The analysis of particle energy transfers, as described by the second moment of the Boltzmann equation, is often necessary within these simulations. We present computationally efficient, analytically derived equations for evaluating collisional energy transfer terms from simulations using discrete particles. The equations are expressed as a sum over the properties of the discrete particles.